KubichV.I., Мarushchak М.М., KurlikovD.A. Condition of the tribological system "SHH15" - lubricating medium - "SHH15" rolling bearings with a stepped load - Кубіч, В. І.; Марущак, М. М.; Курликов, Д. А. (Problems of Tribology, 2018)
The results of tribotechnical tests of the tribological system of materials "SHH15" - lubricating medium - "SHH15", which was investigated in the tribo connection "rolling path - ball - roller path" using the normal roller bearings 305 and 304 with the step load and speeds of the interaction of the friction surfaces 300 , 500, 1000 min-1. In this case, the criterion of the state described is the regularity of the change in the coefficient of rolling friction in the stages of interaction of the surfaces with and without the lubricant material in the conditions of simulation of insufficient lubrication at a steady load and fixed rolling velocities. The study was conducted using SMC-2 friction machine with the use of additional equipment installed on the lower shaft in the form of a transition sleeve. As samples of lubricants, five product consistencies were used: MOLDER MP2; Litol-24; SHRUS; MOTUL TECHGREASE 300; graphite lubrication, and two liquid lubricating media: TAD-17; MT-16P. The main attention is paid to tracking the time, which determined the excess of the permissible value of the coefficient of friction, and the corresponding parameters of power and speed interaction. At 300 min-1, all tested materials did not indicate a critical increase in the friction coefficient during the entire period of operation or during steady state. During the test at 500 min-1, the tribosystem worked on lubricating formations that were already formed. Only the SHRUS, MOTUL, and MT-16P specimens showed the work without exceeding the permissible values, however, as MOLDER, Litol-24, TAD-17 and graphite lubricants had the character of possible destruction of the lubricant layer. With an increase in the speed of up to 1000 min-1, Litol-24 and graphite lubricant, the best indexes of the coefficient of friction are compared with other samples. It should be noted that the samples MOLDER, MOTUL and SHRUS at the beginning of work had an excess of the permissible value, but with increasing load, the coefficient declined and did not cross the limits of the dry friction curve. The obtained results, on the one hand, are relatively generalized and indicate the ambiguous nature of the behavior of the studied lubricants, and, on the other hand, are the starting data for determining the breakthrough time of the lubricating units, which can be used as the basis for the lubrication control algorithm in the rolling bearings. It has been established that the greatest resistance to failure in the conditions under consideration is provided by lubricating units formed from the SHRUS lubricant.